The Impact of Technology on Students’ Psychological and Educational Performance - Taha, Taha Basheer; Abdulrahman, Mohammad Salim (JISA(Jurnal Informatika dan Sains), 2023)
The quality, availability, consistency, and accessibility of technology play vital roles in shaping learning performance and effectiveness. However, it is important to recognize that technology alone does not guarantee desired learning outcomes. Instead, the interaction between humans and technology, along with the design dimensions of educational tools, significantly influence students' learning outcomes and their psychological engagement with the learning process. Moreover, improper utilization of technology can pose obstacles to effective learning. This paper aims to provide a thorough examination of the effects of technology on the learning process, aiming to identify instances where technology serves as a facilitator or hindrance to learners. Furthermore, a diverse range of suggestions will be presented to optimize and enhance the role of technology in promoting effective learning experiences. The research highlighted the advantages and disadvantages of different technology aspects on students, and highlighted how keeping the learning outcome as a principle in course design will lead to the proper evaluation of learning outcome. By delving into these crucial aspects, this research endeavors to provide valuable insights and actionable recommendations for educators, policymakers, and stakeholders seeking to harness the full potential of technology in education.